2021
DOI: 10.1111/aogs.14186
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in migrant women’s maternity care in a high‐income country: A population‐based cohort study of maternal and perinatal outcomes

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
2
11
0
3
Order By: Relevance
“…Furthermore, in a number of studies on immigrant women of sub-Saharan origin in a range of countries such as Norway [ 27 ] and Australia [ 28 ], such sub-Saharan women were seen to present episiotomies and tears (concurrently), to a greater degree. These data are in line with the Gudmundsdottir [ 18 ] study conducted in a migrant population from low-income countries, and with the study by Lorthe [ 29 ], who also found unjustifiable differences in obstetric outcomes in the native and migrant population. According to Wuest [ 30 ], intrapartum third degree tears affecting even the anal passage are common in women subjected to FGM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in a number of studies on immigrant women of sub-Saharan origin in a range of countries such as Norway [ 27 ] and Australia [ 28 ], such sub-Saharan women were seen to present episiotomies and tears (concurrently), to a greater degree. These data are in line with the Gudmundsdottir [ 18 ] study conducted in a migrant population from low-income countries, and with the study by Lorthe [ 29 ], who also found unjustifiable differences in obstetric outcomes in the native and migrant population. According to Wuest [ 30 ], intrapartum third degree tears affecting even the anal passage are common in women subjected to FGM.…”
Section: Discussionsupporting
confidence: 91%
“…Those showing a higher risk were primiparous or multiparous African immigrant women, or from Southern Asia [ 17 ]. Along the same lines, a study conducted in Iceland in 2021 also established worse obstetric outcomes in migrant women from countries with a development index below 0.900 compared to women in the country [ 18 ]. In the bibliography addressing obstetric complications with female genital mutilation [ 4 ], it was shown that women with FGM types II and III were at a greater risk of undergoing caesarean than those not mutilated.…”
Section: Discussionmentioning
confidence: 99%
“…The polytomous categorical variable was based on the Human Development Index (HDI), described in more details in previous research. 1 HDI scores were categorized by IMBR in 12 groups with increments of 0.050. Because of the small number of migrants in Iceland coming from countries with low HDI, we combined the groups in the lower levels based on the number of migrants in each of the twelve categories.…”
Section: Exposure Variablementioning
confidence: 99%
“…The results suggest that factors such as access interfere with quality of midwifery care and might exacerbate inequity in health care. 1 Intrapartum midwifery care is one of the key factors that contributes to quality of care and a woman's positive childbirth experience. 3 Promoting comfort is an integral part of the "art" of midwifery care.…”
Section: Introductionmentioning
confidence: 99%
“…Guðmundsdóttir et al's large study conducted in Iceland between 1997 and 2018 revealed increased odds of several maternal and perinatal complications in refugee women compared with Icelandic women. 13 Although perinatal healthcare is advanced and Open access its services are free in those countries, the authors argued that a large proportion of the refugee women still did not have access to these healthcare services. A recent review by Sturrock et al concluded that despite better healthcare services in high-income countries, refugee mothers still had worse outcomes that may be explained by their late or lack of attendance to antenatal care.…”
Section: Open Accessmentioning
confidence: 99%